TATA KELOLA KELEMBAGAAN ZAKAT DI MALANG: Baznas, EL-Zawa UIN, dan YDSF - Amatul Jadidah; Hairul Puadi (Jurnal Penelitian Ilmiah INTAJ, 2017)
Malang economic growth is quite good and gets positive appreciation in the field of economy, arts, sports, science and so forth, so Malang is dubbed as one of the best cities in Indonesia. Therefore, the availability of adequate institutions that directly touch the needs of the people, in this case, zakat, is necessary. Zakat management institutions should be managed by professional, trustworthy, responsible and knowledgeable. This research uses the qualitative approach of phenomenology which aims to: 1) know the governance of Amil Zakat Institute in the perspective of good governance, 2) reveal the unique social reality of how zakat institutional governance is not a trivial issue but must be planned and organized professionally.The utilization of zakat needs to be done with a priority scale approach with the application of consumptive zakah and productive one. By managing zakat well and advanced will be able to suppress poverty even since mustahiqq become muzakk? because the society is aware of zakat. Improving the economy of the city of Malang is balanced with zakat management institutions such as BAZNAS representing the management of zakat from the role of government, YDSF under the guidance of private LAZ, and El-Zawa guided by the university.